Impact of Tea Tree Cultivation on Soil Microbiota, Soil Organic Matter, and Nitrogen Cycling in Mountainous Plantations - Shuaibo Shao; Yuanping Li; Zhongwei Li; Xiaoxiao Ma; Yanqi Zhu; Yuqing Luo; Pumo Cai; Xiaoli Jia; Christopher Rensing; Qisong Li (Agronomy, 2024)
This study focused on examining the early stages of tea cultivation (1, 3, and 5 years) in mountainous tea plantations. It specifically aimed to investigate the changes in soil micro-ecology at different locations (inter-row, terrace surfaces, and terrace walls). It was revealed that as tea tree cultivation progressed over the years, bacterial diversity and co-occurrence networks annually decreased in different locations. The results of soil physicochemical index analysis showed that the soil’s available nutrients and the activities of cellulase and protease increased. Furthermore, the amplitude of variation of these indexes in the inter-row soil was significantly higher than that on the terrace surfaces and the terrace walls (p < 0.05). Alterations occurred in the soil microbial community structure, with an enrichment of bacterial genera such as Sinomonas, Granulicella, and Sphingomonas, as well as fungal genera such as Trichoderma, Penicillium, and Talaromyces; an increase in the proportion of plant pathogenic fungi (Cladosporium, Fusarium, and Curvularia) was observed in the inter-row soil. The results of soil microbial function prediction showed that nitrification and nitrogen fixation decreased, but denitrification increased (p < 0.05). In conclusion, cultivating tea trees in mountainous terraced plantations significantly impacted the soil microbial community, accelerated the metabolism of soil organic matter, disrupted soil nitrogen cycling functions, and increased the presence of plant pathogenic fungal pathogens. Moreover, the changes in the structure and functions of the soil microbial community demonstrate a spatial distance effect across different terrace locations.